Unraveling how an auxin signaling mutation affects the xylem hydraulic efficiency and safety in tomato - Andrade, Moab Torres de (2022)
Auxins are known to regulate xylem development in plants, however, their effects on water transport efficiency and hydraulic safety are poorly known. Here we used tomato plants of the diageotropica mutant (dgt), which has impaired function of a Cyclophilin 1 cis/trans isomerase involved in auxin signaling, and its corresponding wild type (WT), to explore its effects on plant hydraulics and leaf gas exchanges. The xylem conduits of dgt showed a reduced hydraulically-weighted vessel diameter (D h ) (24-43%) and conduit number (25-58%) in petioles and stems, resulting in lower theoretical hydraulic conductivities (K t ). On the other hand, no changes in root D h and K t were observed. In addition, the measured stem and leaf hydraulic conductances of dgt agreed with the K t values and were lower (up to 81%). Despite dgt and WT showing similar root D h and K t , the measured root hydraulic conductance of dgt was 75% lower. The dgt mutation increased the vein (D v ) and stomata density (D s ), which could potentially increase photosynthesis. Nevertheless, even presenting the same photosynthetic capacity of WT plants, the dgt showed a photosynthetic rate c. 25% lower, coupled with a stomatal conductance reduction of 52%. These results clearly demonstrate that increases in D v and D s only result in higher leaf gas exchange when accompanied by higher hydraulic efficiency. The dgt also showed higher wall thickness per conduit diameter ratio (t/b) 3 , without major modifications in the pit membranes and cell wall reinforcement. The changes in xylem architecture resulted in a more negative Ψ 50 (water potential of 50% loss hydraulic conductivity), with a difference of 0.25 MPa and an increase of 64% in hydraulic safety margin comparison with WT plants. Under water deficit, dgt took twice as many days to reach Ψ 50 (-1.34±0.06 MPa) and half the time after rehydration to recover gas exchange when compared with WT (Ψ 50 = -1.14±0.08 MPa). To confirm that the improved  50 of dgt was functionally significant, we exposed WT plants to a more intense water deficit (equivalent to dgt’s Ψ 50 ) and, indeed, WT plants did not show photosynthetic recovery under this condition. Therefore, we demonstrate that the changes in the xylem as a function of the mutation in auxin perception result in a severe reduction on in hydraulic efficiency and increased hydraulic safety. Keywords: Ailsa Craig. Gas exchange. Solanum lycopersicum. Water deficit. Water transport. Xylem anatomy.